2018
DOI: 10.1590/1983-21252018v31n223rc
|View full text |Cite
|
Sign up to set email alerts
|

Response Function for the Srelative Index in Cambisol Treated With and Without Bovine Liquid Biofertilizer

Abstract: The present study aimed at assessing the influence of physical properties associated with soil structure on the S relative index. Two soil conditions under Ficus carica L. cultivation were studied (with or without liquid bovine biofertilizer in the irrigation water), in the 0-0.1 m and 0-0.3 m layers. Disturbed and undisturbed soil samples were collected from the above-mentioned layers and physical analyzes, pertinent to the study objective, were performed. The response function model was applied to verify how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…Similar behavior was observed for root growth in oiticica (Licania rigida Benth) seedlings irrigated with saline waters (DINIZ NETO et al, 2014). The biofertilizer, through its contribution of humic substances, promoted improvements in physical attributes of the soil, mainly in structure and porosity, which resulted in higher root growth under saline conditions (ALENCAR et al, 2018).…”
Section: Contentssupporting
confidence: 59%
See 2 more Smart Citations
“…Similar behavior was observed for root growth in oiticica (Licania rigida Benth) seedlings irrigated with saline waters (DINIZ NETO et al, 2014). The biofertilizer, through its contribution of humic substances, promoted improvements in physical attributes of the soil, mainly in structure and porosity, which resulted in higher root growth under saline conditions (ALENCAR et al, 2018).…”
Section: Contentssupporting
confidence: 59%
“…The salinity of the irrigation water reduced the ability of the roots to extract water from the substrate, which negatively interfered with photosynthetic processes and CO 2 assimilation, leading to a decrease in cell division and expansion (PARIHAR et al, 2015;NEGRÃO;SCHMÖCKEL;TESTER, 2017). However, because the enriched biofertilizer contained osmoregulatory substances such as potassium, its inclusion promoted greater absorption of water and nutrients by plants (ALENCAR et al, 2018).…”
Section: Contentsmentioning
confidence: 99%
See 1 more Smart Citation
“…observed increases in phosphorus, potassium, calcium, magnesium, and soil organic matter promoted by the Supermagro, even with superiority to the contents of a soil fertilized with NPK. In the cultivation of yellow passion fruit,Cavalcante et al (2011b) observed that the Supermagro promoted the increase of boron, copper, and zinc micronutrients in the soil.Interferences in the microbiological activity and physical properties are the result of an indirect effect of the bovine manure biofertilizer in the soil(Alencar et al, 2018;Wang et al, 2019). In this perspective,Silva et al (2007b) observed that the increase in the doses of Vairo biofertilizer raised the mineralized carbon in the soi.…”
mentioning
confidence: 99%